Prevalence of premature loss of primary teeth among children in Dammam city and parents' awareness toward space maintainers - Laila Abdulwahab AlMeedani; Hebah Zaki Al-Ghanim; Noor Ghazi Al-Sahwan; Sukainah Abdulwahab AlMeedani (Wolters Kluwer Medknow Publications, 2020)
Context: Premature loss of primary teeth is one of the most prevalent dental problems affecting children worldwide. It is commonly caused by dental caries and trauma. Parents are responsible for their children's oral health and should pay close attention to the consequences of space loss. Aims: The aim of this study is to assess the prevalence of premature loss of primary teeth among children in Dammam city, Saudi Arabia and evaluate the parents' awareness toward space maintainers. Settings and Design: A cross-sectional study was planned to randomly select children aged between 4 and 9 years who attend governmental and private clinics in Dammam city. Materials and Methods: WHO criteria (WHO 1997) were used to examine decay-missing-filled index and premature loss of primary teeth. Questionnaires were distributed by hand to the parents of selected children to explore their demographic data and their awareness toward space maintainers. Statistical Analysis: Descriptive statistics were used to describe and summarize data collected numerically by SPSS version 20.0. The level of statistical significance was set at P < 0.05. Data from the questionnaires were analyzed using the following: frequencies, percentages, cross-tabulation, and Chi-square tests. Results: The mean dmf of the participated children in the study was 2.24 (standard deviation = 2.08). The prevalence of premature loss of primary teeth of the selected children was 20%. Only 37 (18.5%) out of 200 parents were aware about space maintainers. Conclusions: The current study revealed a high prevalence of premature loss of primary teeth among children in Saudi Arabia. The parents were unaware about the space maintainer, its used, maintenance, and benefits.